Bureaucratic politics (BP): identifying the causes and elements that contribute to the development of housing projects during the implementation of the National Housing Policy (NHP) - Mohd Zain, Zarina; Ku Samsu, Ku Hasnita; Adnan, Zatul Himmah; Ismail, Mohd Mahadee (Zes Rokman Resources, 2018)
Politics often affects administrative systems, especially when it involves the implementation of government policies and programs. The evident can be seen in the housing development sector where frequent interference from members and political parties in administrative affairs has ultimately undermined the effectiveness of the implementation of a housing project. As a result, there are problems with late-backed housing projects, abandoned projects and ill-reported projects every year resulting peoples received direct impact on the problem, so they cannot afford to have a home to be desired. Most of the study in the housing sector focus mainly on identifying the factors and effects of abandoned housing projects but there has no research done on the effectiveness of the initial process involving the process of evaluation and approval by the authorities to initiate housing development projects where this failure has contributed to the issue of current housing development. Does bureaucratic politics situation really happened in the early stages that contributes to the country's housing issue? Hence, this study focuses on reviewing the management structure during the initial process of housing development project in implementing the National Housing Policy (NHP) to ensure that each housing project is successfully implemented. The main objective of this conceptual paper is to identify the root cause of the intervention or political influence of the bureaucracy (BP) and to evaluate the elements or characteristics that make up the bureaucratic politics situation during the implementation of the housing policy through the housing development project. This paper was written by using secondary data from secondary sources, through library search, journal and articles analysis with reference to several bureaucratic politics models used by previous researchers.